THE TRIASSIC FLORA FROM THE EL TRANQUILO GROUP, PROVINCE OF SANTA CRUZ (PATAGONIA): FOSSIL WOODS (Ameghiniana, 2011)
Anatomical studies of gymnosperms from the Laguna Colorada Formation of El Tranquilo Group (Upper Triassic) from Santa Cruz Province, Argentina, are presented. The following taxa are described: Araucariaceae: Agathoxylon lamaibandianus sp. nov., Agathoxylon dallonii (Boureau) Crisafulli and Herbst comb. nov., Agathoxylon amraparense (Sah and Jain) Crisafulli and Herbst comb. nov.; Podocarpaceae: Podocarpoxylon indicum (Bardwaj) Bose and Maheshwari, Podocarpoxylon paralatifolium Vozenin-Serra and Grant-Mackie, Protophyllocladoxylon sp., and a new species of the ginkgoalean, Ginkgophytoxylon isychozianus Crisafulli and Herbst sp. nov., which is well diferentiated from the other two Permian species of the genus recorded from France, New Mexico (USA) and Uruguay. The validity of the latter genus is discussed and mantained. Some comments are made on the paleoclimatic conditions indicated by the characters of cells of secondary xylem in their growth rings.